ANALISIS FAKTOR-FAKTOR MOTIVASI YANG MEMPENGARUHI MINAT BERWIRAUSAHA - Dion Mahesa, Aditya; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2012)
The study was conducted to determine the student’s motivation and the motivation factors to influence on interest in entrepreneurship. According to the vision and mission of the Faculty of Economics and Business UNDIP, to shape the culture of entrepreneurship we needs to know the motivations of students to further accelerate the establishment of entrepreneurial culture. The target population of this study were students of the Faculty of Economics and Business UNDIP who have taken entrepreneurship courses. The number of samples used was 142 students. This study using a multiple linear regression analysis, where the analysis tool is used to understand the extent of the influence of risk tolerance, self-efficacy in entrepreneurship, and freedom in the work to student’s interest in entrepreneurship. In addition, this study also used ANOVA as the other analysis tools, ANOVA serves as a different test of variance. This study will analyze the differences between student interest in entrepreneurship with a background of parents who worked as an entrepreneur and non-entrepreneurs. The results obtained indicate that all independent variables has a positive and significant effect on the student’s interest to become an entrepreneur, self efficacy was the strongest variable affecting the interest in entrepreneurship. ANOVA test results for different test of variance showed that there was differences students interest in entrepreneurship among parents who work as entrepreneurs and non-entrepreneurs.